Optimization of wheat-lima bean composite flour mixture for chinese noodles (pancit canton) application - Candelaria, Pauline Mae. R.; Gonzales, Benjamin A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This study was conducted to determine the optimal ratio of wheat (WF) and lima bean flours (LBF) for Chinese noodle (pancit canton) application. Lima bean (Phaseolus lunatus L.) flour was produced from raw beans and was mixed in varying ratios with wheat flour using simple lattice mixture design, with a target of 13% protein content. Raw beans were characterized for moisture (62.55±0.08%) crude protein (14.65±0.72) and ash (2.10±0.09) content. The resulting flour was subjected to microbial analyses for aerobic plate count (6.4 x 104 CFU/ml), yeast and mold count (250 CFU/ml), coliforms (2.6 x 102 CFU/ml), E.coli (not detected) and Salmonella (not detected in 25g). The verified optimal ratio of LBF to WF in the composite flour was 1.81:98.19, while the actual protein content was 14.49%. The composite flour, compared to pure wheat, had significantly lower values for water absorption capacity (WAC, 5.03±0.09 vs 5.64±0.23 g/g), water solubility index (WSI, 9.13±0.35 vs 12.26±0.53 w/w), foaming capacity (120.74±1.2 vs 169.44±4.81, %v/v) and foaming stability (110.37±0.64 vs 145.83±7.22 %v/v), but had no significant differences in swelling power (1.30±0.04 vs 1.24±0.03 %v/v), emulsion activity (42.07±0.04 vs 39.61±1.45 %v/v), emulsion stability(45.93±2.13 vs 42.83±1.34 %v/v), and oil absorption capacity (3.16±0.11 vs 3.55±0.10 g/g). . Differences in WAC, WSI, and swelling power were correlated to a negative effect on noodle texture made using composite flour. Consumer acceptability tests between composite and pure wheat flour indicated insignificant differences for appearance, color, taste, and overall acceptability while a significant difference was observed for texture. All mean acceptability ratings were in the range of "like slightly" to "like moderately". The significant difference on the texture of the noodle samples was correlated to the increase in the protein content of the composite flour (14.49) compared to wheat flour (12.37), as well as the effects of the xvii increase in protein content to the functional properties of the composite flour. The overall acceptability score (6.42±0.93), which translates to "like slightly" of the noodle made from the composite flour was used as an indication of the improvement on the protein content of Chinese noodles without severely affecting its overall noodle quality.
submitted June 2017
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Flour